Implantation of HA into superplastic Ti-6Al-4V: Kinetics and mechanical behaviors of implanted layer - Yazdan Parast, Sanaz; Jauhari, Iswadi; Asle Zaeem, Mohsen (Springer Verlag (Germany), 2011)
An implanted layer is produced by implantation of hydroxyapatite (HA) into superplastic Ti-6Al-4V. X-ray diffraction (XRD) analysis indicates that the surface of the implanted layer is composed of HA and Ti-6Al-4V, and line-scanning analysis confirms a mutual elemental diffusion of HA and Ti-6Al-4V. According to the scanning electron microscope (SEM) images, by increasing the implantation temperature, the thickness of the implanted layer increases. The bonding strength between implanted layer and titanium substrate is examined by conducting a friction wear test. Higher surface removal of an implanted layer is observed when as-received Ti-6A1-4V was used in the implantation process, which is an indication of higher bonding strength between implanted layer and superplastic Ti-6A1-4V. The effect of implanted layer thickness on the wear resistance is also investigated. The reduction in thickness of the implanted layer is more evident in thicker implanted layers. The results suggest that the adhesion between the implanted layer and titanium substrate is stronger than the cohesion within the implanted layer. © 2010 The Minerals, Metals & Materials Society and ASM International.